Back cover: Gastrointestinal digestion of hazelnut allergens on molecular level: Elucidation of degradation kinetics and resistant immunoactive peptides using mass spectrometry. Issue 10 (5th October 2017) - Korte, Robin; Bräcker, Julia; Brockmeyer, Jens
Abstract : Mol. Nutr. Food Res . 2017, 61, 1700130. DOI:10.1002/mnfr.201700130 Sensitization to hazelnut allergens via the gastrointestinal tract has been associated with severe clinical symptoms. Therefore, the biochemical fate of six relevant hazelnut allergens undergoing digestion is studied in vitro. Product structures and digestion kinetics are elucidated by HPLC‐MS/MS. 1183 digestion resistant peptides are characterized that may represent sensitizers or elicitors for hazelnut allergy, and a comprehensive insight into the molecular dynamics of the proteolytic degradation of plant food allergens is provided.